Prehospital Medication Administration: A Randomised Study Comparing Intranasal and Intravenous Routes - Cian McDermott; Niamh C. Collins (Emergency Medicine International)
Introduction. Opioid overdose is an ever-increasing problem globally. Recent studies have demonstrated that intranasal (IN) naloxone is a safe and effective alternative to traditional routes of naloxone administration for reversal of opioid overdose. Aims. This randomised controlled trial aimed to compare the time taken to deliver intranasal medication with that of intravenous (IV) medication by advanced paramedic trainees. Methods. 18 advanced paramedic trainees administered either an IN or IV medication to a mannequin model in a classroom-based setting. The time taken for medication delivery was compared. End-user satisfaction was assessed using a 5-point questionnaire regarding ease of use and safety for both routes. Results. The mean time taken for the IN and IV group was 87.1 seconds and 178.2 seconds respectively. The difference in mean time taken was 91.1 seconds (95% confidence interval 55.2 seconds to 126.9 seconds, P≤0.0001). 89% of advanced paramedic trainees reported that the IN route was easier and safer to use than the IV route. Conclusion. This study demonstrates that, amongst advanced paramedic trainees, the IN route of medication administration is significantly faster, better accepted and perceived to be safer than using the IV route. Thus, IN medication administration could be considered more frequently when administering emergency medications in a pre-hospital setting.